2012
DOI: 10.1371/journal.pone.0039307
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Balance between Regulatory T (Treg) and T Helper 17 (Th17) Cells during Hepatitis B Virus Related Liver Fibrosis

Abstract: BackgroundHepatitis B virus-related liver fibrosis (HBV-LF) always progresses from inflammation to fibrosis. However, the relationship between these two pathological conditions is not fully understood. Here, it is postulated that the balance between regulatory T (Treg) cells and T helper 17 (Th17) cells as an indicator of inflammation may predict fibrosis progression of HBV-LF.Methodology/Principal FindingsThe frequencies and phenotypes of peripheral Treg and Th17 cells of seventy-seven HBeAg-positive chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 29 publications
9
99
0
Order By: Relevance
“…6). In addition, several studies have reported that decreased frequency of Treg also results in significantly higher Th17 cells in HBV-infected patients, [58][59][60] which is consistant with our results (Fig. 3D).…”
Section: Discussionsupporting
confidence: 93%
“…6). In addition, several studies have reported that decreased frequency of Treg also results in significantly higher Th17 cells in HBV-infected patients, [58][59][60] which is consistant with our results (Fig. 3D).…”
Section: Discussionsupporting
confidence: 93%
“…is a pro-inflammatory cell that plays vital role on host defenses and several autoimmune disorders through releasing of cytokines such as , and both IL-17A and IL-22 functioned to control of extracellular bacterial infection (Shigematsu et al, 2013). Studies have demonstrated that the level of Th17 cells were significantly increased in patients with liver diseases, additionally, the increasingly level of Th17 cells also promoted the progression of liver fibrosis (Li et al, 2012b). While the levels of IL-17A and IL-22 in the liver tissues were always considered as the main factors to measure liver function.…”
Section: Introductionmentioning
confidence: 99%
“…Our research found that, when compared with healthy people, patients with decompensated cirrhosis have a lower incidence of peripheral Tregs, a higher incidence of Th17, and a Treg/Th17 imbalance. As a result, some researchers consider that Treg and Th17 cells inhibit and promote inflammatory reactions, respectively, and disruptions in the balance between the two contribute greatly to the progression of chronic hepatitis B to cirrhosis and liver failure (Li et al, 2012b). Some researchers have indicated that MSCs can change the composition of T cell subsets, secrete transforming growth factor TGF-β1 and prostaglandin E2, induce the proliferation of Treg cells (De Miguel et al, 2012;Soleymaninejadian et al, 2012), and inhibit the expression of Th17 cells through the CCL2 pathway (Rafei et al, 2009).…”
Section: Discussionmentioning
confidence: 99%